Emergence of uncommon KL38-OCL6-ST220 carbapenem-resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases - Tian, Chongmei; Xing, Mengyu; Fu, Liping; Zhao, Yaping; Fan, Xueyu; Wang, Siwei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To characterize one KL38-OCL6-ST220 carbapenem-resistant Acinetobacter pittii strain, co-producing chromosomal NDM-1 and OXA-820 carbapenemases. Methods A. pittii TCM strain was isolated from a bloodstream infection (BSI). Antimicrobial susceptibility tests were conducted via disc diffusion and broth microdilution. Stability experiments of blaNDM-1 and blaOXA-820 carbapenemase genes were further performed. Whole-genome sequencing (WGS) was performed on the Illumina and Oxford Nanopore platforms. Multilocus sequence typing (MLST) was analyzed based on the Pasteur and Oxford schemes. Resistance genes, virulence factors, and insertion sequences (ISs) were identified with ABRicate based on ResFinder 4.0, virulence factor database (VFDB), and ISfinder. Capsular polysaccharide (KL), lipooligosaccharide outer core (OCL), and plasmid reconstruction were tested using Kaptive and PLACNETw. PHASTER was used to predict prophage regions. A comparative genomics analysis of all ST220 A. pittii strains from the public database was carried out. Point mutations, average nucleotide identity (ANI), DNA–DNA hybridization (DDH) distances, and pan-genome analysis were performed. Results A. pittii TCM was ST220Pas and ST1818Oxf with KL38 and OCL6, respectively. It was resistant to imipenem, meropenem, and ciprofloxacin but still susceptible to amikacin, colistin, and tigecycline. WGS revealed that A. pittii TCM contained one circular chromosome and four plasmids. The Tn125 composite transposon, including blaNDM-1, was located in the chromosome with 3-bp target site duplications (TSDs). Many virulence factors and the blaOXA-820 carbapenemase gene were also identified. The stability assays revealed that blaNDM-1 and blaOXA-820 were stabilized by passage in an antibiotic-free medium. Moreover, 12 prophage regions were identified in the chromosome. Phylogenetic analysis showed that there are 11 ST220 A. pittii strains, and one collected from Anhui, China was closely related. All ST220 A. pittii strains presented high ANI and DDH values; they ranged from 99.85% to 100% for ANI and from 97.4% to 99.9% for DDH. Pan-genome analysis revealed 3,200 core genes, 0 soft core genes, 1,571 shell genes, and 933 cloud genes among the 11 ST220 A. pittii strains. Conclusions The coexistence of chromosomal NDM-1 and OXA-820 carbapenemases in A. pittii presents a huge challenge in healthcare settings. Increased surveillance of this species in hospital and community settings is urgently needed.